CITRA OBJEK WISATA SITUS LAKSAMANA RAJA DI LAUT KABUPATEN BENGKALIS PROVINSI RIAU - Muhammad Sholihin; Firdaus Yusrizal (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
The image is very important for a tourist attraction, that is to know exactly what is in each individual mind on an object, how they understand and what they like or dislike of the object. So as to increase tourist arrivals in tourist attraction. This research aims to know the visitor's perception about image of King Admiral trusted in the Sea Bengkalis Regency Riau Province. This research used a qualitative method with descriptive approach to examine the problems. For first aims use the interview, and for the second aims use Cross Tabulation techniques. The sample in this research were 60 respondents, taken by using accidental sampling. While data collection techniques in this research use observation, questionnaire, documentation and interviews. By using a Likert Scale as a measure to determine the length of the short interval. With sub-variables that are components of the main image (Kennedy 1977) is divided into Values History, Hygiene, Sanitation, Heritage Collection, Conditions Object, Spatial, amenities, Consistency, Accessibility, Security,, hospitality, and comfort. From the results of research conducted in the field of research on Citra attraction King Admiral trusted in the Sea Bengkalis Regency Riau Province was included in the average category.Keywords: Image Tourism Attractions, The heritage, King Admiral at Sea.